Höfundaréttur hugbúnaðar á Íslandi : eru tölvuleikir höfundaréttarvarðir? - Drengur Óla Þorsteinsson 1981- (2012)
This dissertation discusses the copyright of video games under Icelandic law. Copyright has become pressured by the rapid evolution of computer technology the last few decades. This is not only because copy making and distributing has become very easy using of the Internet, but also because the evolution of computer technology is happening faster than law making is able to keep up with. Video games are one product of computer technology and this dissertation discusses how the object of protection in the Icelandic copyright laws fit with video games. Therefore the most important concepts regarding copyright of video games are thoroughly defined. The concepts of copyright, software, software copyright and video games are explained. The history of copyright is examined in the International, European and Icelandic contexts. The most important international conventions on copyright are examined. The status of Icelandic copyright is examined with emphases on software copyright and the question whether video games are copyrighted under Icelandic law. A single judgement of the Supreme Court of Iceland will be looked at as well as the legal definitions and the criteria that computer programs have to fulfil in order to be protected. Finally, the conclusion is that while individual parts of video games are protected but that it is not entirely clear whether a video game, as such, is an object of protection, since it does not fulfil the conditions for protection according to the articles regarding the protection of computer programs and the Supreme Court of Iceland has not clearly indicated in what way video games are protected. Lokaverkefni þetta fjallar um höfundaréttarvernd tölvuleikja á Íslandi. Höfundaréttur hefur orðið fyrir miklum þrýstingi undanfarna áratugi vegna örrar framþróunar tölvutækninnar. Þrýstingurinn er ekki bara vegna þess að afritagerð og dreifing stafræns efnis er auðveld með hjálp alnetsins, heldur einnig vegna þess að tækniframþróunin gerist hraðar en svo að lagasetningar geti með fullkomnum hætti ...